ANALISIS FINANSIAL POKLAHSAR SWAKARYA BERSAMA DI KELURAHAN TANJUNG TENGAH KECAMATAN PENAJAM KABUPATEN PENAJAM PASER UTARA - Hardi Kurniawan; Muhammad Syafril; Gusti Haqiqiansyah (2339-1324, 2020)
The objectives of this study are: (1) Knowing the feasibility of a processed seaweed business measured from the financial aspect (financial). (2) Knowing the driving and inhibiting factors of the seaweed processing business. This research was conducted for 7 months starting in September 2019 until March 2020 in Tanjung Tengah Sub-District, Penajam Regency. The sampling method is taken based on the census method. Data collection was carried out by interviewing the Joint Workshops group with 10 members. The results of the study based on the financial feasibility test of the joint self-cultivation seaweed poklahsar seaweed business in Tanjung Tengah Kelurahan is advantageous with an NVP value of 76 and an IRR value of 33%. While a Net BCR of 1.38 means that the business is feasible and based on the test of driving and inhibiting factors in the Joint Workshops group, the supporting factors are as follows: the availability of raw materials, group cohesiveness, attractive product packaging, attractive product packaging, affordable prices, government assistance, the development of promotional media, high demand, availability of markets, and the limiting factor is the location of the business which is less strategic, ineffective promotion, marketing products classified as local, production capacity is still low, price increases for raw materials, high level of competition, changing consumer tastes, inflation rates that tend to increase.